Job rotation and its relation to the organizational loyalty of the staff of the Education Department - Al Barqi, Maslaha of Bint Hussein (Journal of Economic, Administrative and Legal Sciences, 2017)
The study aimed to find the degree of implementation for Career rotation witch it followed at Education Department at a Laith province, and to now the level of organizational loyalty for the same Education Department. And then to identify the relationship between the degree of implementation for Career rotation and the level of organizational loyalty. And also to now the of differences in the degree of Career rotation and the level of organizational loyalty to the staff for the Education Department at a Laith province depending on the following variables: sex, qualification, experience. Descriptive approach was used because its suitable to this study. Methodology and procedures: Questionnaire has been used to collect the data from The study community, which consists of all the staff of the Education Department (120) employees. Means have been used and standard deviations and Independent Samples T Test and One way anova to analysis the study data. Study results: • Implementation of Career rotation at Education Department at a Laith province was in medium level (2.77). • Organizational loyalty at education department at a laith province was in medium level (2.95). • The study also showed a weak positive relationship between the level of applying career rotation and organizational loyalty for the employees. The value of the correlation coefficient was (263). • A significant difference in the level of applying career rotation according the variables: sex, and experience, while there was no statistically significance difference in the level of applying career rotation according to the qualification variable. • The study also revealed that there is a statistical difference in the level of organizational loyalty according (sex, experience), and there are no statistically significant differences in the level of organizational loyalty according the qualification variable. Recommendations of the study: There is a need to develop a comprehensive and integrated plan to apply the career rotation at the Education Department at Laith province. And Organize Meetings for employees before will be applying the career rotation to explain for them What are the duties and responsibilities for the employee in the new position.